Male child with somatic mosaic Osteopathia Striata with Cranial Sclerosis caused by a novel pathogenic AMER1 frameshift mutation. Issue 7 (12th May 2017) - Hague, Jennifer; Delon, Isabelle; Brugger, Kim; Martin, Howard; Sparnon, Leanne; Simonic, Ingrid; Abbs, Stephen; Park, Soo‐Mi
Abstract : Osteopathia striata with cranial sclerosis (OSCS; OMIM #300373) is a rare X‐linked dominant condition caused by mutations in the AMER1 gene (also known as WTX or FAM123B ). It is a condition which usually affects females in whom the clinical phenotype can be extremely variable. Conversely affected males typically die in utero or during the neonatal period [Perdu et al. (2011 ); Clinical Genetics 80: 383‐388; Vasiljevic et al. (2015 ); Prenatal Diagnosis 35: 302‐304]. There have been a small number of reported cases of surviving males, including three patients who are somatic mosaic for the condition [Chénier, Noor, Dupuis, Stavropoulos, & Mendoza‐Londono, (2012 ); American Journal of Medical Genetics Part A 158A: 2946‐2952; Holman et al. (2011 ); American Journal of Medical Genetics Part A 155A: 2397‐2408; Joseph, Shoji, & Econs, (2010 ); The Journal of Clinical Endocrinology and Metabolism 95: 1506‐1507]. We report a case of a male child who has proven somatic mosaicism for OSCS associated with a novel pathogenic frameshift mutation, c.607_611delAGGCC (p.Arg203 fs) in AMER1 . We describe the multisystemic clinical features which include macrocephaly with ventriculomegaly and requirement for ventriculoperitoneal shunt, cleft palate, and respiratory difficulties after birth requiring tracheostomy insertion, persistent patent ductus arteriosus, failure to thrive and gastrostomy insertion, growth retardation, ophthalmoplegia, kidney malformation, cryptorchidism, and developmental delay. The use of new technologies with next generation sequencing (NGS) may improve the detection rate of mosaicism in rare conditions.